2016
DOI: 10.1097/eja.0000000000000448
|View full text |Cite
|
Sign up to set email alerts
|

Effect of head position on laryngeal visualisation with the McGrath MAC videolaryngoscope in paediatric patients

Abstract: http://cris.nih.go.kridentifier:KCT0001443.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
0
18
1
Order By: Relevance
“…We found that the time to intubation was 24 seconds in the group with support under the shoulder, and the time to intubation was 31 seconds in the group without support under the shoulder. The times in our study were longer than those of Kim et al, but the cause of this difference may be that the age group and the video laryngoscope were different in our study. Additionally, these authors defined the tracheal intubation time as the time between when the researcher picked up and put down the McGrath Video Laryngoscope.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…We found that the time to intubation was 24 seconds in the group with support under the shoulder, and the time to intubation was 31 seconds in the group without support under the shoulder. The times in our study were longer than those of Kim et al, but the cause of this difference may be that the age group and the video laryngoscope were different in our study. Additionally, these authors defined the tracheal intubation time as the time between when the researcher picked up and put down the McGrath Video Laryngoscope.…”
Section: Discussioncontrasting
confidence: 77%
“…In our study, it was found that the placement of a folded towel under the shoulders, considering the alignment of the external auditory canal and sternum in the horizontal plane, increases visualization of the glottis opening. In a study by Kim et al, these authors investigated the effects of head position on laryngeal visualization using the McGrath Mac Video Laryngoscope in children aged 3‐7 years. These authors found a better POGO score and a shorter time to intubation in the group in which the external auditory canal and sternal notch were aligned in the horizontal plane by supporting the head with a pillow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We calculated the sample size based on the POGO score using PASS software (version 15.0; NCSS, LLC, Kaysville, UT, USA). Assuming that a 20% difference in POGO score was clinically important (standard deviation of 35%) [ 30 ], we determined that 28 pairs were required in each sequence for two-sided testing in this 2 × 2 crossover study, with 95% power and an alpha level of 5%. Therefore, we enrolled 32 participants in each sequence group, assuming a dropout rate of 10%.…”
Section: Methodsmentioning
confidence: 99%
“…Thyroidectomy is challenging not only because of the thyroid pathology to be operated on but also because of the anatomic characteristics of young children [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Children are more likely to have recurrent laryngeal nerve (RLN) injury than adults [ 2 ].…”
Section: Introductionmentioning
confidence: 99%